PERBEDAAN KINERJA KEUANGAN DI HARGA SAHAM MURAH DAN MAHAL PADA PERUSAHAAN SUB SEKTOR PROPERTI DAN REAL ESTATE - Muzayyanah, Siti; Choiruddin, Muhammad Nanang (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Property and real estate sector that many people choose to become an investment option and property growth in Indonesia. The purpose of this study is to determine the financial performance of companies and differences in financial performance in stock prices cheap and expensive sub sector of property and real estate. This type of research is descriptive quantitative. The sampling technique used purposive sampling based on predetermined criteria that fit with research purpose. The method used is financial ratios of current ration, return on equity, return on assets, earnings per share and price to earnings ratio and using different test tools. That is Independent sample t-test used to measure differences in financial performance at cheap and expensive stock prices. The results of this study indicate the financial performance in the sub-sector property and real estate has a less good condition. Because of the performance of low-cost and expensive on average has a poor performance despite some companies that have good performance. There is no difference on financial performance in cheap and expensive stock prices which means that cheap stocks are also in good financial condition and not good as well as happening in expensive stock price.